Reverend Canon Alayande’s Contributions to Social Welfare Services in Ibadan, 1959-2006 - Oladele Adeoti, Ezekiel (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Social welfare signifies significant improvement, comfort and well-being of the people. They are services that are targeted at solving social problems, increase social security and promote independence and initiatives of both the individuals and society. They are offered through well-to-do individuals, corporate organizations, government and other agencies. This paper examines Canon Emmanuel Alayande’s contribution to social welfare services in Ibadan and it’s environ between 1959 and 2006. The work highlights Alayande’s contributions to the welfare of groups, youths, the sick and disabled, and those who are mentally challenged. Findings reveal how Alayande utilized his membership of various humanitarian and philanthropic organizations to minister to the various social needs of Ibadan people, particularly children, youth, families with disabilities, elderly persons, and disaster victims, among others. The paper concludes that Canon Alayande contributed in no mean measure to the welfare of the less fortunate members of Ibadan society in many critical areas, such as health, education, rehabilitation of war victims, flood disaster, etc. The data for this work was derived from the following inter-related sources: extant secondary works on Canon Alayande, official documents, newspaper articles, oral and personal interviews with Canon Alayande, his professional colleagues, and the beneficiaries of his social services. The paper concluded that through his selfless support, assistance, initiatives and encouragement, as well as his generosity and devotion to the handicapped and infirm, Canon Alayande turned lives around by rehabilitating and integrating them fully into the society where they contributed their quotas.